Balanced scorecard, behavioural factors and managerial performance of hotels in Malaysia - Abdul Razak, Shazrul Ekhmar (2016)
Performance of hotel operation employees, especially the front-liners and managers is crucial in providing good quality of service to meet various customers’ perceptions and expectations. However, negative behaviour such as lack of direction, motivation and commitment are factors that hamper managers’ performance when they interact with the customers. Prior studies claimed that Balanced Scorecard (BSC) measures can provide information to clarify the roles of employees and motivate them to achieve better performance. Thus, this study intends to extend an earlier model to investigate the relationship between the BSC, behavioural factors and managerial performance in hotel sector in Malaysia. Specifically, this study investigates the mediating effect of behavioural factors (role clarity, psychological empowerment and organizational commitment) between the use of BSC measures and managerial performance. Goalsetting theory is adopted to explain the relationship between the variables. Data for the study was collected using questionnaire, which were distributed to managers of 3, 4, and 5-star hotels in Malaysia. Structural Equation Model (SEM) using AMOS 22.0 was employed to analyse the data. The findings indicated that the use of BSC is significantly associated with increased role clarity, enhanced psychological empowerment and improved organizational commitment, and these behavioural factors also have significant effect on managerial performance. These behavioural factors also appear to significantly mediate the relationship between BSC and managerial performance, in consistent with goal setting theory. These results provide information to Malaysian Association of Hotels and Ministry of Tourism and Culture for policy making decisions.